The impact of telecommunication technologies on competition in services and goods markets: Empirical evidence - Vahagn Jerbashian; Anna Kochanovay (International Telecommunications Society (ITS), 2012)
In this paper we empirically show that a more intensive use and wider adoption of telecommunication technologies significantly increases the level of product market competition in services and goods markets. Our result is consistent with the view that the use of telecommunication technologies can lower the costs of entry. This finding is robust to various measures of competition and a range of specification checks.
Keywords: L16; O33; O25; 330; Telecommunication technologies; Entry costs; Product market competition